Mirror feedback in Zumba dance education: effects on proprioception, balance and mood state - Acar, Gizem Ceylan; Tuncel, Semiyha (Peerj Inc, 2026)
Background This study aims to investigate the effects of Zumba dance training conducted in a mirrored environment on participants' knee joint position sense (proprioception), static-dynamic balance and mood state. Methods A total of 39 female volunteers aged 18 to 25 participated in the study. Participants were randomly and counterbalanced assigned to three groups: mirror Zumba training group (n = 14), non-mirror Zumba training group (n = 13), and a control group (n = 12). Zumba sessions were held for 10 weeks, three times per week, one hour per session. Data collection took place at Ankara University, Faculty of Sports Sciences, Performance Laboratory. Participants visited the laboratory four times and underwent assessments for body composition (body mass index (BMI)), knee joint position sense, static and dynamic balance, and mood using the Positive and Negative Affect Schedule (PANAS). Results Zumba training performed in front of mirrors significantly impaired knee joint proprioception (p < .05). The mirror group showed reduced proprioceptive sensitivity at 15 degrees, 16 30 degrees, 60 degrees, and 90 degrees knee angles, whereas the non-mirror group demonstrated significant improvement at the same angles. Mirror use also negatively affected static balance while facilitating dynamic balance. However, no significant differences were found in mood states between groups, indicating that mirror presence did not impact emotional well-being. Conclusions The use of mirrors during Zumba dance training may disrupt proprioceptive development and static balance, although it can enhance dynamic balance. Since mirror use did not influence mood, its impact appears primarily physical. These results suggest that mirrors in group exercise settings should be used selectively, especially when the goal is to enhance proprioception.
Keywords: Mirror; Dance; Mood; Training; Joint Position Sense; Static-Dynamic Balance